'DEMOCRATIZING' PUBLIC SERVICES? REPRESENTATION AND ELECTIONS IN THE SCOTTISH NHS. (30th June 2014) - GREER, SCOTT L.; WILSON, IAIN; STEWART, ELLEN; DONNELLY, PETER D.
<x xml:space="preserve">Abstract</x> In representative democracies most public administration is actually directed by unelected appointees. These appointees are accountable to voters only indirectly through a minister. In Scotland, many decisions on healthcare provision are made by regional health boards. The Scottish government authorized experimental elections to two of these health boards in the hope of democratizing health service administration. Our research uncovered many unexpected consequences of holding direct elections to health boards, but they did not revolutionize the accountability structure in the ways we might have expected. New members largely accepted inherited norms which discouraged them from acting as conduits for public opinion.